The diagnostic yield of transesophageal echocardiography in patients with cryptogenic cerebral ischaemia: a meta‐analysis. (19th November 2015) - Katsanos, A. H.; Giannopoulos, S.; Frogoudaki, A.; Vrettou, A.‐R.; Ikonomidis, I.; Paraskevaidis, I.; Zompola, C.; Vadikolias, K.; Boviatsis, E.; Parissis, J.; Voumvourakis, K.; Kyritsis, A. P.; et al.
Abstract : Background and purpose: The diagnostic utility of transesophageal echocardiography (TEE) in patients with cryptogenic ischaemic stroke (IS) or transient ischaemic attack (TIA) remains controversial. Methods: A systematic review and meta‐analysis was performed according to PRISMA guidelines to estimate the pooled prevalence of potential cardioembolic causes detected by TEE in prospective observational studies of cryptogenic IS/TIA. Cardiac conditions causally associated with cerebral ischaemia were considered to be intramural thrombi and intracardiac tumors according to ASCO phenotyping of IS. Results: Thirty‐five eligible studies, comprising 5772 patients (mean age 53.6 years, 56.9% men) were identified. The most common TEE finding was ascending aorta and/or aortic arch atheroma [51.2% (27.4%–74.5%)], followed by patent foramen ovale (PFO) [43.2% (36.3%–50.4%)]. Complex aortic plaques and large PFOs were reported in 14% (10.2%–18.9%) and 19.5% (16.6%–22.8%) of TEE evaluations. The prevalence of atrial septal aneurysm was 12.3% (7.9%–18.7%) and was significantly higher in conjunction with PFO presence (risk ratio 2.04, 95% confidence interval 1.63–2.54, P < 0.001). The prevalence of left atrial thrombus [3.0% (1.1%–8.3%)] and spontaneous echo contrast [3.8% (2.3%–6.2%)] was low. The prevalence of intracardiac tumors was extremely uncommon [0.2% (0%–0.7%)]. Significant heterogeneity was identified ( I 2 > 60%) in the majority of analyses. Heterogeneity was not affected by cryptogenic stroke definition (TOAST versus alternative criteria). After dichotomizing available studies using a cut‐off of 50 years, PFO was significantly ( P = 0.001) more prevalent in younger than in older patients. Conclusion: Routine TEE in patients with cryptogenic IS/TIA commonly identifies abnormal findings. However, the prevalence of cardiac conditions considered to be causally associated with cerebral ischaemia (intracardiac thrombi and tumors) is low.